The Competitive Advantages of Small and Medium Enterprises in Xayabuly District, Xayabouly Province - INDAVONG, dalounny; Soudthida Hoongsengpha, Soudthida; Phanthouamath, Poutthalack; Sengchanh, souksamone; Chitaphone, Namfonh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this research were to study the operational competitive advantages of small and medium sized enterprises in Xayabouly district, Xayabouly Province, to Study the strategic management factors within the organization of small and medium sized enterprises in Xayabouly district, Xayabouly Province and to study the organization management strategic factors influence the competitive advantage in the operation of small and medium-sized enterprises in Xayaburi District, Xayaburi Province. The research was conducted by using a questionnaire as an instrument for collecting data from 320 SMEs Entrepreneurs in the Xayabouly district, Xayabouly Province. The Cronbach alpha reliability coefficient was 0.969. The statistics used for data analysis were frequency, percentage, mean, standard deviation, Multiple Regression analysis. The results revealed that: The operational competitive advantages of SMEs in Xayaburi district were generally found to have highly competitive advantages, which included: operating cost advantages, followed by differentiation advantages, rapid response advantages, and segmentation advantages. The strategic management factors within the organization of small and medium-sized enterprises in Xayaburi District, Xayaburi Province were generally used in the operation at a good level, which includes: the personnel factor, the work system factor, the strategic factors, the skill, knowledge / ability factor, the shared value factor and the structural factors of the organization. The strategic management factors within the organization influence the competitive advantage in the operation of small and medium-sized enterprises in Xayaburi District, Xayaburi Province were included: the skill knowledge / ability factor, the strategic planning factor, the management style, personnel factor and the operation system factor.